Care partner needs of people with neurodegenerative disorders: What are the needs, and how well do the current assessment tools capture these needs? A systematic meta‐review. (6th June 2022) - Kinchin, Irina; Edwards, Layla; Adrion, Emily; Chen, Yaohua; Ashour, Aya; Leroi, Iracema; Brugulat‐Serrat, Anna; Phillips, Jane; Masterson, Fiona; Kochovska, Slavica
Abstract: Objectives: The burden on care partners, particularly once dementia emerges, is among the greatest of all caregiving groups. This meta‐review aimed to (1) synthesis evidence on the self‐reported needs of care partners supporting people living with neurodegenerative disorders; (2) compare the needs according to care partner and care recipient characteristics; and (3) determine the face validity of existing care partner needs assessment tools. Methods: We conducted a systematic review of reviews involving a thematic synthesis of care partner needs and differences in needs according to demographic and other characteristics. We then conducted a gap analysis by identifying the themes of needs from existing needs assessment tools specific to dementia and cross‐matching them with the needs derived from the thematic synthesis. Results: Drawing on 17 published reviews, the identified range of needs fell into four key themes: (1) knowledge and information, (2) physical, social and emotional support, (3) care partner self‐care, and (4) care recipient needs. Needs may differ according to disease trajectory, relationship to the care recipient, and the demographic characteristics of the care partner and recipient. The 'captured needs' range between 8% and 66% across all the included needs assessment tools. Conclusions: Current tools do not fully or adequately capture the self‐identified needs of care partners of people living with neurodegenerative disorders. Given the high burden on care partners, which has been further exacerbated by the COVID‐19 (SARS CoV‐2) pandemic, the needs assessment tools should align with the self‐reported needs of care partners throughout the caregiving trajectory to better understand unmet needs and target supportive interventions. Key points: This is a synthesis of available research in the area of needs of care partners of people living with neurodegenerative disorders. Needs identified by care partners fall into four broad themes (1) knowledge and information, (2) physical, social and emotional support needs, (3) care partner self‐care, and (4) care recipient needs. This research highlights the mismatch between the care partners' needs and the needs captured by the needs assessment tools. This meta‐review identified emerging needs that have not been explored by existing needs assessment tools and demonstrated the importance of individualized assessment of the relative importance of needs throughout the caregiving trajectory.